Comparison of Microstructural and Mechanical Properties of Hydroxyapatite-ZrO2 Composites with Commercial Inert Glass Addition - ERKMEN, ZİYA ENGİN (SPRINGER-VERLAG BERLIN, 2014)
Hydroxyapatite(HA) is very popular bioceramic for hard tissue restorations. But, bulk HAs are not suitable for load bearing applications. So, HA material can be reinforced with a second phase (i.e polymers, metals and ceramics) to make a stronger composite material. The aim of this study is to compare the microstructural and mechanical properties of HA-ZrO2 composites with the addition of 5 and 10 wt % commercial inert glass (CIG), separately. The green samples were produced according to BS 7253 at 350 MPa. Then, they were sintered at between 1000 and 1300 degrees C for 4 h. Microstructural properties of the obtained composites were characterized using SEM (Scanning electron microscopy) + EDS; phase analysis was done by X-ray diffractometer (XRD), mechanical properties were measured by compression and hardness tests. According to the results of ongoing bioactivity and biocompatibility studies, these two composites will possibly be good candidates for orthopedical applications.